The Correlation Between Adjective Mastery And Students’ Writing Descriptive Text At SMA Swasta Persiapan Stabat - Efrini Panjaitan; Elga Elga (English Teaching and Linguistics Journal (ETLiJ), 2020)
The objective of study is investigated correlation between adjective mastery and students’ writing descriptive text of the tenth grade students of SMA Swasta Persiapan Stabat. The study is a correlation research. It is aimed at finding out whether there is any significant correlation between the adjective mastery and students’ ability in writing descriptive text. The population is 244 and the sample is 44 which took by lottery technique. The data analysis used Product Moment formula. It can be concluded that there is a significant correlation between the adjective mastery and writing descriptive text ability of the 2017/2018 tenth year students of SMA Swasta Persiapan Stabat. This is proved from the analysis that the coefficient correlation between the students’ adjective mastery and writing descriptive text ability is 0.78. Compared with the degree of correlation, it is categorized as a strong and significant correlation. Therefore, the hypothesis of the study is accepted.